IMPLEMENTATION OF PROJECT-BASED LEARNING IN SPEAKING LEARNING: A CASE STUDY ON THIRD SEMESTER STUDENTS AT IAINU TUBAN - Ali Fauzi; M. Rizky Fathoni Al Maliki (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
English plays a crucial role as an international language for communication and for the advancement of science and technology. In Islamic higher education, English instruction aims to develop students' proficiency in the four essential language skills: listening, speaking, reading, and writing. Among these, speaking is often regarded as one of the most challenging skills to master. This study investigates the implementation of Project-Based Learning (PjBL) in a speaking course for third-semester students at IAINU Tuban. Using a qualitative case study design with a phenomenological approach, data were collected through classroom observations, semi-structured interviews with students, and documentation during the English Communication course. The data were analyzed descriptively to explore students' learning experiences and the instructional process. The findings indicate that the implementation of Project-Based Learning effectively enhanced students' speaking performance by engaging them in collaborative projects that required academic writing, oral presentations, and interactive classroom discussions. Students demonstrated greater confidence, active participation, higher motivation to practice English, and improved ability to communicate their ideas orally. Furthermore, the integration of writing and speaking activities promoted a more meaningful learning experience and strengthened students' overall English proficiency. The study suggests that Project-Based Learning is an effective instructional model for improving speaking skills while simultaneously fostering collaborative learning and academic communication in English language classrooms.